EXAMINATION OF TRANSITION IMPROVISATIONS OF NECDET YAŞAR’S IN TERMS OF MODAL AND TECHNICAL CONSTITUTION - Hüseyin Serdar ÇAKIRER (Fırat University, 2019)
One of the most effective and important tanbur palyer Necdet Yaşars’ modal and technical analyse of transition improvisations constitutes the subject of this study. According to other instruments of Turkish Classical Music tanbur has low saund volume. Necdet Yaşar have developed stronger plectrum stroke in order to obtain sound reproduction and has integrated left hand agility with his plectrum stroke intensity. in order to support this right and left hand technique with the various movements, he has benefited from the towing sounds by applying the volume slide (glissando) technique to tanbur instrument. On the other hand, formatting bağlama’s particular plectrum stroke with tanbur he often give place to folk music themes in his improvisations. These applications finds out various sounds of tanbur better. It also gains new musical dynamics to better performance. For this reason, tanbur improvisations that made by Necdet Yaşar hold an important place in Turkish Classical Music and hold place at state conservatory İn Turkey. This study includes Necdet Yaşar’s works, who has carried Tanburi Cemil’s ecole to our times through his son Mesut Cemil and has combined it with his own technique. Necdet Yaşar, who has been accepted as one of the most prominent Tanbur virtuoso of the music circle and whose curriculum of the tunes of the Turkish state conservatory and the variety of improvisations in his works have been analysed. Initially, his accessable improvisations were first put into notes. And then, the improvised notes were technically analysed and scrutinized from the point of form. This study has been limited with the 5 improvisations of Necdet Yaşar that can be reached.